Teaching an Integrated Reading and Writing Course During the COVID-19 Pandemic in University Context: A Lecturer's Voice - Susanah, Susanah; Thabran, Yulhenli; Kurniati, Erisa; Hendri, Hendri (Universitas Jambi, Magister Program of English Education Department, 2025)
Drawing upon Teo's (2013) model of critical reading and writing stages and Moseley's (2005) Integrated model for understanding thinking and learning, this qualitative case study aimed to explore the lecturer's knowledge of teaching the integrated reading and writing course and his experience of teaching the course using synchronous Case-Based Learning (CBL) during Covid-19 Pandemic. Data were collected through online classroom observations and semi-structured interviews. The findings indicated that the lecturer designed the Critical Reading and Writing course to develop students' critical arguments from multiple worldviews; however, he perceived that CBL failed to meet the course's objectives due to student-related problem factors. Students' under-achieving level of critical thinking skills and their problems in terms of English proficiency, learning disengagement, and hesitance to explore unfamiliar phenomena contributed to the unsuccessful implementation of the CBL. Pedagogical implications are highlighted for future research